A novel concept to determine the optimal heating mode of residential rooms based on the inverse problem method. (February 2015) - Hua, Jing; Fan, Hongming; Wang, Xin; Zhang, Yinping
Abstract: Because heating energy consumption is huge and it takes a large part of building energy consumption, techniques aiming at decreasing the heating energy demand are very important in today's world. While, there are few studies regarding the determination method of the optimal heating mode (i.e. convective, radiative or mixing) of a given house. A novel concept based on the inverse problem method to determine the optimal heating mode of residential rooms is put forward in this paper. By minimizing the additive heating energy consumption and keeping indoor thermal comfort simultaneously, the optimal heating mode of residential rooms is determined by the variation method. Some general conclusions are derived, such as the transition point of the convective and radiative heating mode and the influence of wall's thermophysical properties on the energy saving ratio. For illustrative purposes, a typical residential room in Beijing is analyzed. In addition, optimal heating modes of six typical room kinds in four representative cities in China are determined, which can guide the proper selection of the heating method in various places. The proposed method can be the first step to build the optimal indoor thermal network, and the new concepts can be used to deal with other similar problems in the built environment field. Highlights: With inverse problem and variation method, analytical solution is put forward. Relationship between the optimal heating method and building's parameters is studied. Physical explanation and an easy way to approach the optimal method is put forward.